Vztah typologie a konstrukční soustavy - Čechová, Pavla (Vysoké učení technické v Brně. Fakulta architektury)
využití stávajících konstrukcí, panelové stavby, systém panelových staveb T06B, rozpon, nosné části konstrukce, úpravy konstrukce, model řešení

utilization of current structures, concrete buildings, system of concrete buildings T06B, spank, portative parts of the structure, structure modifications, model of the solution
Relationship typology and structural system
Keywords: Práce se zabývá možnostmi úprav systému T06B; který patří k nejrozšířenějším soustavám panelových staveb s množstvím variant. Principy tohoto příčného systému s rozponem 3600mm základní nosné struktury umožňují množství variant úprav i doplnění konstrukce. Jsou zobrazeny modely a schémata možných řešení úprav.; My work deals with possibilities of structure system modifications T06B; which belongs to the most widespread systems of concrete buildings with many varieties. The principles of this transverse system with a basic portative structure spank of 3600 mm allow many varieties of modifications and replenishments. In the work are represented models and charts of possible solutions of modifications.